Power spectral density analysis of ocean wave by using GPS buoy - Mohd Salleh, Anuar; Daud, Mohd Effendi (International Journal of Integrated Engineering, 2018)
Wave buoy equipped with a mechanical or electrical sensor have been used extensively to observe waves around the world but the integration of GPS technology with wave buoy (GPS buoy) only has been explore usefulness in this field in the early 90's. This study presents the capabilities of GPS buoy to observe wave data at Strait of Malacca by using high precision kinematic positioning approach. The GPS buoy data obtained from this observation were processed through a precise, medium-range differential kinematic technique. These data were observed at a high rate (1 Hz) interval over a period of more than 24 hours from a nearby coastal site. The kinematic coordinates of the GPS buoy were estimated via epoch-wise pre-elimination and the backward substitution algorithm. These kinematic coordinates are used to calculate the magnitude of the Power Spectral Density (PSD). PSD analysis function able to shows the strength of the variations (energy) as a function of frequency. The tidal changes and monsoon wind has been found to greatly influence the wave energy as shown in the PSD analysis.Â  From the test result, GPS buoy and data processing technique promises a total solution as a complete ocean wave monitoring solution for Strait of Malacca.